2017
DOI: 10.1097/pec.0000000000000653
|View full text |Cite
|
Sign up to set email alerts
|

Can Telemedicine Improve Adherence to Resuscitation Guidelines for Critically Ill Children at Community Hospitals? A Randomized Controlled Trial Using High-Fidelity Simulation

Abstract: This study demonstrates the feasibility of using telemedicine to support acute management of children who present to community hospitals. Neither study arm adhered to current resuscitation guidelines and telemedicine consultation with PCCM experts was not associated with improvement. However, further research on optimizing telemedicine impact on the quality of pediatric care at community hospitals is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Although limited in number, 86% of these demonstrated improvements in healthcare quality and safety, providing a positive "proof of concept" that pediatric care in community hospitals can be improved by multidisciplinary efforts and be sustained over time. [43][44][45][46][47]49,[51][52][53][54][55][56] As pediatric depart- ments within community hospitals may have limited resources, aligning pediatric QI efforts with adult initiatives within the same hospitals could prove advantageous. However, we did not identify any studies meeting our inclusion criteria that took this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although limited in number, 86% of these demonstrated improvements in healthcare quality and safety, providing a positive "proof of concept" that pediatric care in community hospitals can be improved by multidisciplinary efforts and be sustained over time. [43][44][45][46][47]49,[51][52][53][54][55][56] As pediatric depart- ments within community hospitals may have limited resources, aligning pediatric QI efforts with adult initiatives within the same hospitals could prove advantageous. However, we did not identify any studies meeting our inclusion criteria that took this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have suggested improved quality of care in the ED or ICU for critically ill or injured children at rural hospitals lacking paediatric subspecialty care with the use of telemedicine consultations 24 25. Other studies have evaluated adherence to clinical resuscitation guidelines, as well as the use in paediatric critical results with varying results in clinical outcomes, but overall positive acceptability 23–29…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine has been defined as “technology‐enabled health and care management and delivery systems that extend capacity and access.” More recently, the benefits of telemedicine have been recognized by the healthcare community and have been increasingly used to enhance the accessibility of tertiary care for children, particularly in rural and underserved areas . In the adult arena, telemedicine has been shown to be effective for the management of multiple cancer‐related symptoms, including pain .…”
Section: The Challenge: Optimizing Cancer Pain Management For Childrementioning
confidence: 99%
“…64 More recently, the benefits of telemedicine have been recognized by the healthcare community and have been increasingly used to enhance the accessibility of tertiary care for children, particularly in rural and underserved areas. 65,66 In the adult arena, telemedicine has been shown to be effective for the management of multiple cancer-related symptoms, including pain. 67 In pediatric oncology, telemedicine has been utilized to improve access to care and has been effective in improving cancer-related outcomes.…”
Section: Telemedicinementioning
confidence: 99%